Simultanes Löten von Anschlußkontakten elektronischer Bauelemente mit Diodenlaserstrahlung - Fröhlich, Thomas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2002)
Laser soldering in electronics production is a selective and contact-free soldering method for leaded components and allows even joining in a thermally sensitive environment. Special beam forming and guiding units combined with several diode lasers are integrated in a laser soldering system which has advantages for an automated soldering system with a high productivit